Tasks and Content of procedural Guidance of Pre-Trial Investigation of Criminal Offenses Committed by a Group of Persons - O. V. Pchelina (Bulletin of Kharkiv National University of Internal Affairs)
The author has carried out analysis of scientific approaches to the interpretation of the concept and meaning of the institution of procedural guidance of pre-trial investigation in general, as well as taking into account the specifics of criminal offenses committed by a group of persons. It has been argued that the procedural guidance of pre-trial investigation is one of the functions of the prosecutor aimed at ensuring the effectiveness of criminal proceedings, which is undoubtedly implemented as a procedural form of interaction with the relevant pre-trial investigation agencies. It has been emphasized that the procedural guidance of pre-trial investigation of criminal offenses in general and those committed by a group of persons plays an important role in ensuring the effective implementation of the tasks of criminal proceedings. Procedural guidance of pre-trial investigation of criminal offenses committed by a group of persons has been defined as one of the functions of a prosecutor aimed at timely detection of criminal offenses committed by a group of persons, their effective pre-trial investigation, protection of rights and freedoms of lawful participants in criminal proceedings, on overcoming the opposition to pre-trial investigation of such offenses, which is implemented as a procedural form of interaction with the relevant pre-trial investigation agencies. The content of the procedural guidance of pre-trial investigation of criminal offenses committed by a group of persons has been revealed. It has been offered to present the content of the specified procedural guidance to the following groups of powers of the prosecutor: powers aimed at timely detection of criminal offenses committed by a group of persons, their effective pre-trial investigation; powers aimed at protecting the rights and freedoms of lawful participants in criminal proceedings; powers aimed at overcoming the opposition to pre-trial investigation of criminal offenses committed by a group of persons.